2014
DOI: 10.1016/j.polymer.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of highly crystallized polyethylene

Abstract: We report thermal conductivity (κ) of low-density, high-density and ultra-high density polyethylene (PE) with different crystallinity and microstructures. PE was crystallized under high-pressure and high-temperature conditions which produce extended chain crystals. By applying a two-phase model, we estimate κ of 100% crystallized PE as a function of pressure and temperature. The increased crystallinity and lamellar thickness (fold length) reduce the thermal resistance, which is reflected not only in the absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 26 publications
2
61
0
Order By: Relevance
“…As it is described previously, the crystalline structures of semicrystalline polymer matrix, including crystal form and the degree of crystallinity, exhibit apparent influence on the thermal conductivity of semicrystalline polymer based nanocomposites [7,22]. For example, Yu et al [22] found that the increased crystallinity and lamellar thickness (fold length) reduced the thermal resistance of material.…”
Section: Crystallization Behavior Of Pvdfmentioning
confidence: 90%
See 1 more Smart Citation
“…As it is described previously, the crystalline structures of semicrystalline polymer matrix, including crystal form and the degree of crystallinity, exhibit apparent influence on the thermal conductivity of semicrystalline polymer based nanocomposites [7,22]. For example, Yu et al [22] found that the increased crystallinity and lamellar thickness (fold length) reduced the thermal resistance of material.…”
Section: Crystallization Behavior Of Pvdfmentioning
confidence: 90%
“…For example, Yu et al [22] found that the increased crystallinity and lamellar thickness (fold length) reduced the thermal resistance of material. They also proposed that it was crucial to increase the lamellar thickness to significantly enhance the thermal conductivity of semicrystalline polymers.…”
Section: Crystallization Behavior Of Pvdfmentioning
confidence: 99%
“…Compared to manipulating polymer chain alignment to form specic orientations [7][8][9] and yield high crystallinity 10,11 in the matrix to obtain high thermal conductivity, doping llers with high thermal conductivity into polymers is a simple and effective way to improve the thermal conductivity of composites. However, the type, [12][13][14][15] dimensions, [16][17][18][19] size 20,21 and concentration 22,23 of the ller are factors that play signicant roles in the thermal conductivity of composites.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene (PE) has semicrystalline structure with roughly equal parts of crystalline and amorphous domains due to the orientation of the methylene main chain [1]; vastly used in industrial applications because of their mechanical properties [2]. The precise degree of crystallinity and density are dependent on the molecular weight (Mw) of PE, giving rise to classification into low-density PE (LPDE, Mw ≈ 50,000), high density PE (HDPE, Mw ≈ 200,000) and ultrahigh molecular weight PE (UHPE, Mw ≈ 3,500,000 -7,500,000) [3].…”
Section: Introductionmentioning
confidence: 99%